2009
DOI: 10.1007/s00127-008-0492-0
|View full text |Cite
|
Sign up to set email alerts
|

Emotional over-involvement can be deleterious for caregivers’ health

Abstract: In a sample of 37 Mexican American caregivers and their ill relatives recruited from two outpatient clinics, we examined the relationships between EOI, caregiver burden, caregivers' level of social support, and caregivers' health. Additionally, we examined whether caregiver burden and social support may mediate the relationship between EOI and caregivers' health. Cross-sectional analysis indicates that at baseline EOI was not associated with caregiver burden or social support, but was related to worse current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 35 publications
0
19
0
2
Order By: Relevance
“…There have been many studies on both the relationship between EE and depression in patients (Hayhurst, Cooper, Paykel, Vearnals, & Ramana, 1997;Hinrichsen, Adelstein & Mcmeniman, 2004;Silk et al, 2009) and the association between EE and the caregivers' health among patients with schizophrenia (Breitborde et al, 2009;Breitborde, L opez, & Kopelowicz, 2010). A number of studies have also found that EE in caregivers of dementia patients was related to caregivers' strain and distress (Bledin, MacCarthy, Kuipers, & Woods, 1990), burden (Nomura et al, 2005;Vitaliano, Russo, Young, Teri, & Maiuro, 1991), and psychological well-being (Gilhooly & Whittick, 1989).…”
Section: Introductionmentioning
confidence: 97%
“…There have been many studies on both the relationship between EE and depression in patients (Hayhurst, Cooper, Paykel, Vearnals, & Ramana, 1997;Hinrichsen, Adelstein & Mcmeniman, 2004;Silk et al, 2009) and the association between EE and the caregivers' health among patients with schizophrenia (Breitborde et al, 2009;Breitborde, L opez, & Kopelowicz, 2010). A number of studies have also found that EE in caregivers of dementia patients was related to caregivers' strain and distress (Bledin, MacCarthy, Kuipers, & Woods, 1990), burden (Nomura et al, 2005;Vitaliano, Russo, Young, Teri, & Maiuro, 1991), and psychological well-being (Gilhooly & Whittick, 1989).…”
Section: Introductionmentioning
confidence: 97%
“…As for social psychological factors, social support, family function, and family coping have been the most reported significant factors predicting family burden, with consistent evidence showing that better social support[4, 3336], higher level of family function [3739], as well as positive coping styles [20, 40] were associated with decreased family burden.…”
Section: Introductionmentioning
confidence: 99%
“…Within a large sample of prospective FTF participants at entry to the program, parents of youth (18 years and younger) with mental illness reported more problems with their child’s difficult behaviors, greater concern with youth’s dependency on parents to coordinate care and support daily living, greater concern with the effect of mental illness on their families, and higher levels of stigma, anxiety, and depression relative to parents of adults (19 years and older) with mental illness [21]. Caregiving obligations, perceptions of burden, and fragmentation of youth service systems for family members of youth with mental illness may leave them more vulnerable to mental and physical health concerns of their own, and less equipped to play an optimally supportive role in their children’s treatment and recovery [2225]. …”
Section: Introductionmentioning
confidence: 99%